1995
DOI: 10.1097/00005392-199508000-00103
|View full text |Cite
|
Sign up to set email alerts
|

Ureterocele Associated with Ureteral Duplication and a Nonfunctioning Upper Pole Segment

Abstract: We reviewed the records of 87 patients with a ureterocele associated with duplication and a nonfunctioning upper pole segment. All patients involved in this study were treated by partial nephroureterectomy and observation. Additional surgery to correct vesicoureteral reflux became necessary in 54 cases (62%). A careful retrospective chart and radiographic review identified that the need for additional surgery was directly related to the number of renal moieties that had a ureterocele or vesicoureteral reflux p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…However, there are some authors who recommend preservation even these small portions of functioning parenchyma and avoiding partial nephrectomy [7], but others advocate a more extensive reconstruction consisting of partial nephroureterectomy with ureter reimplantation in those patients with ectopic ureterocele with a nonfunctioning pole and coexisting reflux [1, 3, 4]. In our series, the majority of patients had a poorly functioning ureterocele moiety – <20% – which was determined by either DMSA or DTPA renal scan.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, there are some authors who recommend preservation even these small portions of functioning parenchyma and avoiding partial nephrectomy [7], but others advocate a more extensive reconstruction consisting of partial nephroureterectomy with ureter reimplantation in those patients with ectopic ureterocele with a nonfunctioning pole and coexisting reflux [1, 3, 4]. In our series, the majority of patients had a poorly functioning ureterocele moiety – <20% – which was determined by either DMSA or DTPA renal scan.…”
Section: Discussionmentioning
confidence: 88%
“…The traditonal treatment of ureterocele associated with duplication includes upper pole partial nephrectomy with or without ureterocele incision and, if needed, ureteric reimplantation through a separate surgical approach [1, 4]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further 5 studies were excluded as they were duplicate publications. Ten further studies were excluded for the following reasons: 8 studies included paediatric patients as well as adults, with no differentiation of results and outcomes [15-22]; one study was excluded as it was a clinical review of the topic with no data presented [23]; and lastly, one publication was excluded as it investigated the utility of heminephrectomy for horseshoe kidney rather than duplex kidney [24]. One study was found through the searching of reference lists of included articles.…”
Section: Resultsmentioning
confidence: 99%